Parents' experiences with interprofessional collaboration in neonatal pain management: A descriptive qualitative study - Mäki-Asiala Mariaana; Axelin Anna; Pölkki Tarja (WILEY, 2025)
Aim: To describe parents' experiences with interprofessional collaboration (IPC) in neonatal pain management.BackgroundNeonatal care should be based on IPC, and non-pharmacological pain-relieving methods are recommended to be used primarily that enables parental participation. However, there is a lack of knowledge about pain management on IPC from the parent's viewpoint.
Design: A descriptive qualitative study.
Method: The research involved a purposive sample of parents (n = 16) whose infant had been treated at a neonatal intensive care unit in Finland. Interviews were conducted with participants from all over Finland who were recruited through the national association for premature infants. Parents discussed their experiences during semi-structured interviews which were guided by the subareas of IPC, partnership, cooperation and coordination. The data were analysed using deductive-inductive content analysis. The reporting of results followed COREQ guidelines.
Results: Based on the parent's experiences the partnership involved themes of understanding the neonatal pain management context, being able to influence the pain management, and feeling valued. Cooperation included themes of identifying different roles and equality. Coordination was described through the sharing of knowledge, skills and expertise, as well as feeling supported by professionals.
Conclusion: Parental involvement on IPC should be developed through interventions that involve training around pain assessment and non-pharmacological pain-relief methods.
Relevance for clinical practice: Professionals involved in neonatal care should act in a goal-oriented and unified manner to promote a culture of care that allows for active parental participation.
No patient or public contribution: The research has been carried out in accordance with good scientific practice. Only the research team has been involved in the design, conduct, analysis and drafting of the manuscript.